2015
DOI: 10.1186/s12943-015-0364-7
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA, CCDC26, controls myeloid leukemia cell growth through regulation of KIT expression

Abstract: BackgroundAccumulating evidence suggests that some long noncoding RNAs (lncRNAs) are involved in certain diseases, such as cancer. The lncRNA, CCDC26, is related to childhood acute myeloid leukemia (AML) because its copy number is altered in AML patients.ResultsWe found that CCDC26 transcripts were abundant in the nuclear fraction of K562 human myeloid leukemia cells. To examine the function of CCDC26, gene knockdown (KD) was performed using short hairpin RNAs (shRNAs), and four KD clones, in which CCDC26 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 48 publications
1
61
0
Order By: Relevance
“…In fact, recently, hepatic lncRNAs are reported to be involved in the progression of liver fibrosis (He et al, 2014;Yu et al, 2016;Zheng et al, 2015). Previous GWAS studies revealed some SNPs within the lincRNAs as disease associated (Hirano et al, 2015;Radtke et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recently, hepatic lncRNAs are reported to be involved in the progression of liver fibrosis (He et al, 2014;Yu et al, 2016;Zheng et al, 2015). Previous GWAS studies revealed some SNPs within the lincRNAs as disease associated (Hirano et al, 2015;Radtke et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As lncRNAs have emerged as important participants in the pathogenesis and disease progression of AML, [66][67][68][69][70][71][72][73][74] it is likely that profiling of their expression would have significant impact on MDS prognostication. Recently, it has been shown that lncRNA expression signatures were closely associated with specific mutations and a small subset of lncRNAs could predict clinical outcome in cytogenetically normal elderly AML patients, 75 but the clinical significance of lncRNA profiling in MDSs has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have tissue-specific expression and serve an important role in the human transcriptome by regulating normal tissue differentiation as well as cancer development (30). Notably, a number of previous studies have implicated a role of lncRNA dysregulation, of transcripts including leukemia-induced non-coding activator RNA, B-ALL-associated long RNA (BALR)-6 and -2, NOTCH1-associated lncRNA in T-ALL and CCDC26, in tumorigenicity in leukemias (31)(32)(33)(34). SNPs may significantly influence gene expression and function.…”
Section: Discussionmentioning
confidence: 99%